2019
DOI: 10.1029/2018jb016757
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Changes Before and After Earthquakes Based on Long‐Term Measurements of Multiple Parameters at Two Sites in Northern Iceland—A Review

Abstract: Hydrochemical changes before and after earthquakes have been reported for over 50 years. However, few reports provide sufficient data for an association to be verified statistically. Also, no mechanism has been proposed to explain why hydrochemical changes are observed far from earthquake foci where associated strains are small (<10−8). Here we address these challenges based on time series of multiple hydrochemical parameters from two sites in northern Iceland. We report hydrochemical changes before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 33 publications
0
67
1
1
Order By: Relevance
“…As a result, it is very difficult to relate the geochemical anomalies to a specific process and prove that are really associated with earthquakes. Despite this, water chemical anomalies are increasingly recorded at distances between 20 km and more than 200 km from strong earthquake epicenters (Andrén et al, 2016;Chen et al, 2015;Claesson et al, 2004;De Luca et al, 2018;Grant et al, 2011;Huang et al, 2012;Igarashi et al, 1995;Inan et al, 2012;Ingebritsen & Manga, 2014;Sano & Wakita, 2016;Skelton et al, 2008Skelton et al, , 2014Skelton et al, , 2019Wakita et al, 1988;Wang & Manga, 2010;Wästeby et al, 2014;Zeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is very difficult to relate the geochemical anomalies to a specific process and prove that are really associated with earthquakes. Despite this, water chemical anomalies are increasingly recorded at distances between 20 km and more than 200 km from strong earthquake epicenters (Andrén et al, 2016;Chen et al, 2015;Claesson et al, 2004;De Luca et al, 2018;Grant et al, 2011;Huang et al, 2012;Igarashi et al, 1995;Inan et al, 2012;Ingebritsen & Manga, 2014;Sano & Wakita, 2016;Skelton et al, 2008Skelton et al, , 2014Skelton et al, , 2019Wakita et al, 1988;Wang & Manga, 2010;Wästeby et al, 2014;Zeng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical anomalies created by earthquakes have been explained by the mixing of fluids from different sources (with different chemical compositions) inhibited by changes in flow pathway geometry and hydraulic properties during stress build-up and failure 15,16 . Laboratory studies have also observed the emergence of concentration anomalies in noble gases during rock deformation experiments [17][18][19][20] .…”
mentioning
confidence: 99%
“…300 m). The dimensions of the conduit and paleoflows are not visible in the seismic profiles, for example the Christmas-tree structures described by Somoza et al (2003). From previous literature (e.g., Kioka and Ashi, 2015), we can only infer that the BMV dimensions and its computed volume suggest a polygenetic behavior, so we argue that the main fluid conduit has possibly been utilized several times to increase the volume of the volcano itself.…”
Section: Morphologymentioning
confidence: 69%